ТЕХНОЛОГІЇ ФОРМУВАННЯ ЕКОЛОГІЧНОЇ СВІДОМОСТІ СТУДЕНТІВ ПРИРОДНИЧИХ ФАКУЛЬТЕТІВ У ПРОЦЕСІ НАВЧАЛЬНО-ВИРОБНИЧОЇ ПРАКТИКИ (Педагогіка вищої та середньої школи, 2007)
This article is devoted to the technologies of forming ecological consciousness of students at Biology Departments during their practical work. The model of forming ecological consciousness the method of planning ecological activity, ways and means of effective formation of perspective Biology teachers’ are considered in the work ecological consciousness.